International management : culture, strategy, and behavior - Luthans, Fred; Doh, Jonathan P. (New York : McGraw Hill Education, 2015)
For the new ninth edition we have incorporated important new content in the areas of sustainability and sustainable management practices, the emergence and role of social media as a means of transacting business around the world, the rise of emerging market...
Environmental foundation -- The role of culture -- International strategic management -- Organizational behavior and human resource management
Includes bibliographical references and index.
Keywords: INTERNATIONAL BUSINESS ENTERPRISES